2018
DOI: 10.1021/acsanm.8b01624
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning of Polymer-Coated Gold Nanohybrids: Sensor for the Selective Detection of Quinalphos and Device Fabrication for Water Purification

Abstract: Noble polymer P 1 was synthesized and utilized to produce organic nanoparticles (ONPs). The ONPs were used to formulate Au@ONP nanohybrids. The Au@ONP was subsequently fine-tuned for the selective detection of quinalphos via decorating Cu 2+ on its surface. The selective detection of quinalphos in an aqueous medium was achieved, and a detection limit of 2.4 nM was obtained. To validate triple-layered Cu(II)-Au@ONP for quinalphos sensing, simulated real sample analysis was done. Finally silica coating of Cu(II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In fact, various receptors having thiol or other sulfur-containing moieties can covalently tether metallic and metal oxide surfaces. 56,57 More harsh approaches towards these linkages include metal-carbon (by aryl diazonium derivatives), 58 metal-carbene or metal-nitrene (via diazo derivatives), 59 or metal-acetylide/-vinylidene (via acetylene derivatives) 60 covalent bonds. Despite its weaker interactions, amines, ammonium ions, negatively charged carboxylate groups and phosphines can also be used for the effective NP functionalization.…”
Section: D Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, various receptors having thiol or other sulfur-containing moieties can covalently tether metallic and metal oxide surfaces. 56,57 More harsh approaches towards these linkages include metal-carbon (by aryl diazonium derivatives), 58 metal-carbene or metal-nitrene (via diazo derivatives), 59 or metal-acetylide/-vinylidene (via acetylene derivatives) 60 covalent bonds. Despite its weaker interactions, amines, ammonium ions, negatively charged carboxylate groups and phosphines can also be used for the effective NP functionalization.…”
Section: D Nanostructuresmentioning
confidence: 99%
“…Depending on the recognition event, the sensor readout can be a change in the optical properties, 56,[91][92][93]95,96,104,105,110,113 or in the electrical characteristics 98,108 of 0D nanostructures. The extraordinary optical properties of metallic NPs due to the plasmonic phenomenon have given rise to the rapid development of colorimetric sensors.…”
Section: Sensors Based On 0d Ldmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Huerta-Aguilar et al have prepared fluorometric gold nanosensor (FONPs) used to recognize the cysteine and cytosine in real samples, [22] Rani et al have designed the polymer-coated gold nanohybrid which had sensed the quinalphos with enhanced fluorescence emission signal. [23] Prathap et al have reported imidazole-based gold complexes (NHCÀ Au(I)) to direct clinical determination of glucose. [24] Kaur et al prepared silver nanoparticles decorated with reduced graphene oxide for ascorbic acid, dopamine, uric acid, and tryptophan.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the preparation of MNPs in an aqueous solution by using polymers as stabilizing agents has been reported. Rani et al [ 2 ] synthesized thiourea-linked polymer as a starting entity to develop a sensor for quinalphos detection. Huerta-Aguilar et al [ 3 ] used thiophene-based organic nanoparticles decorated with AuNPs to detect cysteine and cytosine in real samples, such as Saccharomyces cerevisiae cells.…”
Section: Introductionmentioning
confidence: 99%